Integrative transcriptomic-physiological analysis deciphers nitrogen-mediated carbon reallocation balancing growth and flavonoid metabolism in Epimedium pubescens - Liu, Shangnian; An, Xiaojing; Xu, Chaoqun; He, Dongmei; Li, Xianen; Chen, Caixia; Guo, Baolin; Xu, De; Huang, Juan (Frontiers in Plant Science, 2025)
Nitrogen availability critically shapes medicinal plant quality by coordinating the “growth–secondary metabolism” trade-off, yet its regulatory mechanisms remain elusive in the non-model species Epimedium pubescens. Through physiological-transcriptomic integration under five nitrogen levels (0, 3.5, 7.5,15, 22.5 mM NO3−), we demonstrated that moderate nitrogen (MN: 7.5 mM NO3−) optimally balanced biomass accumulation (22%–53% higher than low nitrogen [LN: 0 mM NO3−] and high nitrogen [HN: 22.5 mM NO3−]) with maximal Icariin-type flavonoid production (19%–34% higher than LN/HN). Extreme nitrogen stresses (LN/HN) impaired photosynthetic efficiency (18%–20% reduction), disrupted carbon–nitrogen homeostasis, and restricted flavonoid biosynthesis by hindering carbon reallocation (soluble sugars reduced by 26%–27%, starch by 30%–43%). Time-series transcriptomics revealed distinct response dynamics: LN triggered active transcriptional reprogramming at mid-stage (36 days after treatment, DAT), whereas HN responses were delayed to late-stage (48 DAT). Weighted gene co-expression network analysis (WGCNA) identified the grey60 module as a hub coordinating carbon–nitrogen metabolism and mRNA processing. A tripartite regulatory network linking nitrogen-responsive genes (e.g., EpF3H, UGT), Icariin-type flavonoid/carbon metabolism (e.g., icariin, soluble sugars), and growth phenotypes (e.g., biomass, photosynthesis) elucidated how nitrogen optimizes the trade-off between medicinal quality and yield in E. pubescens. This study provides molecular targets for precision nitrogen management to enhance both medicinal quality and yield, while establishing an integrative framework combining physiological and transcriptomic analyses to investigate metabolic trade-offs in non-model plants.